2012
DOI: 10.1001/jama.2012.110980
|View full text |Cite
|
Sign up to set email alerts
|

Association Between World Trade Center Exposure and Excess Cancer Risk

Abstract: Among persons enrolled in the World Trade Center Health Registry, there was an excess risk for prostate cancer, thyroid cancer, and myeloma in 2007-2008 compared with that for New York State residents; however, these findings were based on a small number of events and multiple comparisons. No significant associations were observed with intensity of World Trade Center exposures. Longer follow-up for typically long-latency cancers and attention to specific cancer sites are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
133
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(149 citation statements)
references
References 31 publications
12
133
1
Order By: Relevance
“…Persons with 9/11 exposure, PTSD, or both face increased risk for numerous conditions also associated with smoking (U.S. Department of Health and Human Services, 2014), such as cardiovascular disease (Ahmadi et al, 2011;Boscarino, 2008;Jordan et al, 2011;Jordan et al, 2013;Spitzer et al, 2009), certain cancers (Li et al, 2012;Zeig-Owens et al, 2011), respiratory problems (Brackbill et al, 2009;Maslow et al, 2012;Nair et al, 2012), and diabetes (Agyemang et al, 2012;Boyko et al, 2010;Miller-Archie et al, 2014). The combination of 9/11 exposure and PTSD makes smokers exposed to 9/11 a particularly vulnerable subgroup with increased risk for myriad negative health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Persons with 9/11 exposure, PTSD, or both face increased risk for numerous conditions also associated with smoking (U.S. Department of Health and Human Services, 2014), such as cardiovascular disease (Ahmadi et al, 2011;Boscarino, 2008;Jordan et al, 2011;Jordan et al, 2013;Spitzer et al, 2009), certain cancers (Li et al, 2012;Zeig-Owens et al, 2011), respiratory problems (Brackbill et al, 2009;Maslow et al, 2012;Nair et al, 2012), and diabetes (Agyemang et al, 2012;Boyko et al, 2010;Miller-Archie et al, 2014). The combination of 9/11 exposure and PTSD makes smokers exposed to 9/11 a particularly vulnerable subgroup with increased risk for myriad negative health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…noted 8 cases of MM, four of them were younger than 45 years4. This observation was supported by another longitudinal study of 55,778 New York State residents, which revealed excess incidence in responders for MM5. In the present report, we provide evidence revealing that WTC dust is potent in inducing mdig in normal B cells and MM cells and further demonstrating that mdig is significantly associated with the malignant transformation of MGUS to active MM, disease exacerbation and poor clinical outcomes.…”
mentioning
confidence: 52%
“…1A). Since concerns had been arisen about the potential for increased risk of MM among WTC responders45, we also investigated the capability of WTC dust on the induction of mdig in normal B cells using a B cell line C5B7. Similar to what we observed in BEAS-2B cells, we noted a dose-dependent induction of mdig protein and mRNA by WTC dust in C5B7 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, the Lancet Journal published a report that concluded seven years after the September 11th attacks, showing a 19% increase in total cancer rates among World Trade Center debris exposed New York City firefighters [2]. In a separate study published by Li et al [3], cancer risk was monitored among 9-11 rescue and recovery workers from 2003 to 2008. This study reported an increased incidence of prostate, thyroid, and myeloma cancers emerging in the later years of the study.…”
Section: Introductionmentioning
confidence: 99%